Promoting Physical Activity and Quality of Life Post Liver Transplant in Saudi Arabia - Moussa, Mahaman (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Background: In 2013, approximately 25,029 liver transplants were conducted in 112 international states and countries, including Saudi Arabia. Post liver transplant patients may experience higher health related quality of life (HRQOL), compared to preoperative status, for up to 20 years. Multiple researchers have found that patient engagement in physical activity improves their HRQOL. However, post liver transplant patients often do not engage in physical activity. In addition, in Saudi Arabia, no intervention is in place to promote physical activity among this population.Purpose: The purpose of this project was to determine if a walking program (physical activity) for post liver transplant patients improved HRQOL for this patient population.Methods: This study was a prospective evaluation of the walking program. The target population was post liver transplant patients from one tertiary hospital in Riyadh. Patients included were between the ages of 18 and 69 years. Data on patients’ levels of physical activity were collected using the International Physical Activity Questionnaire (IPAQ) and data on patients’ HRQOL were collecting using the SF-12 Version 1.Results: A total of 20 patients were invited to participate in the study. Of those 20 patients, 15 patients signed the consent. All the 15 patients who participated in this study were able to complete the 7 week walking program. SF-12 and IPAQ data were collected for all 15 patients at Week 1 and at Week7. At baseline, patients’ metabolic equivalent (MET) scores ranged from 99 to 628.5 and at Week 7, their scores ranged from 1402.5 to 3006.Patients showed improvement in all HRQOL domains except the emotional domain.